EFFECTS OF FLOOD ON LIVELIHOOD ACTIVITIES OF SMALLHOLDER CROP FARMERS IN SAKI WEST LOCAL GOVERNMENT AREA, OYO STATE, NIGERIA - ADEKOLA, O. A.; ADESIJI, G. B.; ADETARAMI, O.; OOSE, M. O.; KOMOLAFE, S. E. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2023)
This study was conducted to examine the effect of flood on the livelihood activities of smallholder crop farmers in Oke-ogun, Saki West Local Government Area, Oyo State. Specifically, it identified the livelihood activities of farmers, assessed the effects of floods, and identified adaptation measures adopted by the farmers. Multiple sampling techniques were used to select 120 respondents for the study. A structured interview schedule was used to collect primary data. The result shows that the majority (60.0% and 85.0) of the respondents were male and married. Root and tuber production (75.0%), vegetable farming (75.0%), agro-marketing (66.7%), and arable cropping (66.7%) were the leading livelihood activities of respondents. All (100.0%) of the respondents reported that flood has caused heavy erosion and damage to farm infrastructures and food insecurity while another majority (85.0%) indicated damage to farm roads, loss of farm crops, livestock destruction, and malaria sickness. Also, crop rotation (90.0%), shifting cultivation (85.0%), early planting (75.0%), prevention of soil erosion (75.0%), and cover crop (60.0%) were the main flood adaptation measures with less planting of flood resistance seeds (45.0%) by respondents. Inferential analyses showed that respondents’ marital status (χ2=29.400), educational status (χ2=18.00), age (r = 0.282), and experience in farming (r = 0.301) showed a significant relationship at p≤0.05 level of significance with the effects of the flood on livelihood activities of respondents. The study concluded that smallholder farmers were engaged in agricultural livelihood diversification including root and tuber production, vegetable farming, arable cropping, plantain production, and animal rearing, which have been adversely affected by flood disaster. Therefore, farmers should intensify efforts in the cultivation of flood-resistant varieties while extension agents should assist farmers in timely access to flood-resistant seeds.